The effect of using technology in teaching and learning mathematics on student’s mathematics performance: The mediation effect of students’ mathematics interest - Bright, Asare; Welcome, Natalie B.; Arthur, Yarhands D. (Journal of Mathematics and Science Teacher, 2024)
The current study aimed to determine the impact of using technology in mathematics teaching and learning on the mathematics performance of students as mediated by students’ interest in mathematics. Simple random sampling techniques were used to sample 216 students from the three selected SHS in Kumasi, Ghana. A structured questionnaire was used as an instrument for data collection since the study is purely quantitative. Amos (ver. 23) was used to analyze the structural paths of the study. The results from the analysis reveal that the impact of technology on mathematics performance was positive and significant, and the impact of mathematics interest on mathematics performance was positive and significant. Also, the impact of technology on mathematics interest was positive and significant. Finally, the connection between employing technology in mathematics teaching and learning and students' performance in mathematics is somewhat mediated by students' interest in mathematics, and this relationship is statistically significant. The Ghana Education Service and the Ministry of Education were further advised by the study to incorporate technology into mathematics instruction and learning to boost senior high school students' interest and performance in the subject.